2024
DOI: 10.1002/eat.24168
|View full text |Cite
|
Sign up to set email alerts
|

Lower region‐specific gray matter volume in females with atypical anorexia nervosa and anorexia nervosa

Amanda E. Lyall,
Lauren Breithaupt,
Chunni Ji
et al.

Abstract: ObjectiveFew studies have focused on brain structure in atypical anorexia nervosa (atypical AN). This study investigates differences in gray matter volume (GMV) between females with anorexia nervosa (AN) and atypical AN, and healthy controls (HC).MethodStructural magnetic resonance imaging data were acquired for 37 AN, 23 atypical AN, and 41 HC female participants. Freesurfer was used to extract GMV, cortical thickness, and surface area for six brain lobes and associated cortical regions of interest (ROI). Pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…Moreover, this relative difference in bodyweights is more representative of clinical AN. For example, in ABA models, AN rodents are often ~35%–45% smaller compared to control animals (Scharner & Stengel, 2021 ), whereas in clinical studies the difference between healthy controls and those with AN typically ranges from 20% to 30% (Keeler et al., 2024 ; Kerruish et al., 2002 ; Lyall et al., 2024 ). Importantly, none of our animals required euthanasia due to excessive weight loss, low body condition score, or dramatic changes in behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this relative difference in bodyweights is more representative of clinical AN. For example, in ABA models, AN rodents are often ~35%–45% smaller compared to control animals (Scharner & Stengel, 2021 ), whereas in clinical studies the difference between healthy controls and those with AN typically ranges from 20% to 30% (Keeler et al., 2024 ; Kerruish et al., 2002 ; Lyall et al., 2024 ). Importantly, none of our animals required euthanasia due to excessive weight loss, low body condition score, or dramatic changes in behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Despite not being underweight, individuals with atypical AN can also develop structural brain changes similar to those seen in AN. Using structural magnetic imaging, Lyall et al (2024) found that gray matter volumes in the frontal, temporal, and parietal areas were lower than healthy controls in both atypical AN and AN, with no significant differences between atypical AN and AN. In a large cohort of adults hospitalized for medical instability, Gibson et al (2024) found that both weight suppression and recent weight loss were predictive of some of the physiological changes of malnutrition, but low BMI better predicted medical complications than either weight suppression or recent weight loss.…”
mentioning
confidence: 94%